If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -1(8x + 6) = 42 Reorder the terms: 12x + -1(6 + 8x) = 42 12x + (6 * -1 + 8x * -1) = 42 12x + (-6 + -8x) = 42 Reorder the terms: -6 + 12x + -8x = 42 Combine like terms: 12x + -8x = 4x -6 + 4x = 42 Solving -6 + 4x = 42 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 4x = 42 + 6 Combine like terms: -6 + 6 = 0 0 + 4x = 42 + 6 4x = 42 + 6 Combine like terms: 42 + 6 = 48 4x = 48 Divide each side by '4'. x = 12 Simplifying x = 12
| 2000+25a=4750 | | 4/3-7/15/6/5 | | m-21-5m=3m-2+4m | | 2000+25a=0 | | 4(3-2)+4= | | x^2/2+9x/14-5/7=0 | | 4(3-2)+4=8 | | 6x-2=-2(x+9) | | 5(4+3)+5= | | 2.5x=12.4 | | 2lnx+1lnx^2=3 | | (0.7x+17)-2(8x-4)= | | 2lnx+1lnx^23= | | x/4+3/x=7/4 | | x+4/3=3x^2 | | 53/-5 | | 4x^2-5x=2 | | 3+3(2x-6)=15 | | P^2+16p+64=22 | | 2a+9=14 | | 6+2(x-2)=28 | | 1/2x+1/4x=13+11 | | -2x-14+4x=6 | | 4(2x-6)-3x=6 | | 2(x+7)+2x=42 | | -3.2=l+(0.2) | | (.2)(3x+5)=8 | | 5(x+3)+5=40 | | x+6=8-x | | 3x^2-375=0 | | 10x+8=8x+24 | | x+3x=8-x |